URGENSI KEMENTERIAN AGAMA KABUPATEN BARRU DALAM MENENTUKAN STANDAR DAN VALIDASI ARAH KIBLAT - Tasliyah Erlina; Saleh Ridwan; Kurniati (Universitas Islam Negeri Alauddin Makassar, 2022)
This study examines the role of the government in this case the Ministry of Religion of Barru Regency in overcoming problems related to religious affairs, one of which is the difference in the direction of Qibla in the community. Qibla direction is very important to know because it greatly affects the quality of worship (acceptance of prayer or not) that is done. In determining the Qibla direction, various methods are used, including using a istiwaini, compass, Qibla arc, and Qibla tracker. This research is classified as field research, with a normative (syar'i) and juridical theological research approach where the data that is considered relevant in the object of this research is studied in depth and then poured into a discussion in accordance with the existing problems, including those related to its existence in determining the Qibla direction and the implementation process in measuring the Qibla direction. Keywords: Ministry of Religion, Qibla Direction and Method